2014
DOI: 10.1136/tobaccocontrol-2014-051804
|View full text |Cite
|
Sign up to set email alerts
|

Toxic metal and nicotine content of cigarettes sold in China, 2009 and 2012

Abstract: BACKGROUND Metals of primary health concern can accumulate in the tobacco plant and contribute to smokers’ exposures to carcinogens, a significant cause of the millions of smoking-related deaths in China each year. These exposures are due to the smoker’s addiction to nicotine. OBJECTIVE This study sought to explore toxic heavy metal and nicotine concentrations in the tobacco of Chinese cigarette brands purchased in 2009 and 2012, as well as its regional variation. METHODS Cigarette packs for this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Nitrogen generally produces the greatest growth response in plants of all fertilizer nutrients (Davies et al, 2001). On the other hand, the fertilizer may contain heavy metals like As, Cd, Cr, Ni, and Hg, which can be transferred to tobacco and be correlated with nicotine concentration (O'Connor et al, 2015). Therefore, some percentage of Hg and Cd content in tobacco may have resulted from fertilizer application to the soil upon which the tobac- co plant is cultivated.…”
Section: The Correlations Of Nicotine With Hg CD and Pb Concentration In Cigarettesmentioning
confidence: 99%
“…Nitrogen generally produces the greatest growth response in plants of all fertilizer nutrients (Davies et al, 2001). On the other hand, the fertilizer may contain heavy metals like As, Cd, Cr, Ni, and Hg, which can be transferred to tobacco and be correlated with nicotine concentration (O'Connor et al, 2015). Therefore, some percentage of Hg and Cd content in tobacco may have resulted from fertilizer application to the soil upon which the tobac- co plant is cultivated.…”
Section: The Correlations Of Nicotine With Hg CD and Pb Concentration In Cigarettesmentioning
confidence: 99%
“…A study of cigarette brands from different cities in China showed varying and high levels of heavy metals, suggesting that the use of fertilizers and pesticides may also contribute to these differences in the tobacco samples evaluated (O'Connor et al 2015). High rates of oral cancer were found in regions contaminated with heavy metals (Yuan et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Elemental fingerprints are typically detected using inductively coupled plasma mass spectrometry (ICP-MS), however, this technique is not practical for rapid on scene diagnostics that are required by U.K. Trading Standards and HMRC due to time constraints and the need for aggressive digestion methods that destroy evidence vital for criminal convictions [8,13]. X-Ray fluorescence (XRF) has previously been scaled down and applied for safe handheld use as an economical and sensitive technique to provide a bulk elemental profiles of plant foliage in under 15 seconds, easily translatable to tobacco analysis [14][15][16].…”
Section: Elemental Analysis Of Tobaccomentioning
confidence: 99%